Self‐reflection, growth goals, and academic outcomes: A qualitative study. (26th December 2014) - Travers, Cheryl J.; Morisano, Dominique; Locke, Edwin A.; Martin, Andrew
<x xml:space="preserve">Abstract</x> Background Goal‐setting theory continues to be among the most popular and influential theories of motivation and performance, although there have been limited academic applications relative to applications in other domains, such as organizational psychology. Aims This paper summarizes existing quantitative research and then employs a qualitative approach to exploring academic growth via an in‐depth reflective growth goal‐setting methodology. Sample The study focuses on 92 UK final‐year students enrolled in an elective advanced interpersonal skills and personal development module, with self‐reflection and growth goal setting at its core. Method Qualitative data in the form of regular reflective written diary entries and qualitative questionnaires were collected from students during, on completion of, and 6 months following the personal growth goal‐setting programme. Results About 20% of students' self‐set growth goals directly related to academic growth and performance; students reported that these had a strong impact on their achievement both during and following the reflective programme. Growth goals that were indirectly related to achievement (e.g., stress management) appeared to positively impact academic growth and other outcomes (e.g., well‐being). A follow‐up survey revealed that growth goal setting continued to impact academic growth factors (e.g., self‐efficacy, academic performance) beyond the reflective programme itself. Conclusions Academic growth can result from both academically direct and indirect growth goals, and growth goal setting appears to be aided by the process of simultaneous growth reflection. The implications for promoting academic growth via this unique learning and development approach are discussed.